OTU-013 Outcomes of 360 HALO express radio-frequency ablation for barrett's oesophagus related neoplasia. (8th June 2018) - Magee, Cormac; Gordon, Charles; Dunn, Jason; Zeki, Sebastian; Penman, Ian; Willert, Robert; Smart, Howard; Fernandez-Sorto, Jacobo; Ragunath, Krish; Pana, Mirela; Pietro, Massimiliano Di; Ravi, Narayanasamy; et al.
Abstract : Introduction: Radio-frequency ablation (RFA) for the treatment of Barrett's oesophagus (BE) related neoplasia ablative intervention after endoscopic resection (ER)For circumferential BE, the 3 cm HALO 360. balloon used to treat large areas. A new device, the HALO 360 Express self-sizing catheter was recently launched and can potentially allow quicker ablation times and better coverage of the mucosa due to the improved tissue/catheter contact and 4 cm balloon length. We have previously presented initial data of 3 month follow up in these patients but now present more extensive data including end of treatment biopsies. Method: Specialist centres in the UK and Ireland submitted cases where Halo 360 express had been used. Patients returned for follow up at 3 months after index RFA express treatment. surface area regression of BE regression of intestinal metaplasia (EoT (End of Treatment) CR-IM) and dysplasia (EoT CR-D) were analysed.[MDP1] . Results: 11 centres submitted 123 patients treated with the HALO 360 Express catheter. 112 of these cases had 3 month follow up. The mean age was 67 years±10. 83% were male. 43 patients (35%) had low grade dysplasia (LGD) as initial histology; 62 had high grade dysplasia (HGD) 50%, 19 had intramucosal carcinoma (15%), 1 had invasive adenocarcinoma. 54 (44%) had had previous endoscopic mucosal resection (EMR).The mean pre-treatment circumferential Barrett's segment was 5.5 cm ±4.3 cm and the mean mucosal length (M) was 7.8 cm ±3.6 cm mean% reduction in C of 78%±36% and mean reduction in M of 55%±36% at this first 3 month follow up. 17 patients developed strictures which required dilation at this 3 month follow up. The median number of dilations was 2 (IQR2–4). 4/17 (24%) were treated with 12J/no clean, 10/17 were treated with 10J/no clean (59%), 3/17 (17%) had been treated with 10J/clean protocol. 8/17 (47%) had had previous EMR. 47 patients had 12 month EoT biopsies, 40 (85%) had CR-D and 34 (76%) had CR-IM. 4/112 patients (<4%) had progressed to invasive cancer at the time of writing. The median number of treatments (focal RFA, EMR, APC (argon plasma coagulation)) to EoT was 2(IQR1–4). Conclusions: The HALO 360 Express catheter shows good reduction in C and M length at 3 months, and effective eradication of IM and Dysplasia in those at 12 months. However, as previously reported by us the stricture rate is high.